Aliphatic, alicyclic, and saturated heterocyclic chemistry a review of the literature published during 1970 and 1971 /: a review of the literature published during 1970 and 1971. Five- and six-membered rings, medium-sized rings, bridged and caged systems (carbocyclic and saturated heterocyclic) : Volume I, part III, (1973) - Unknown
No abstract available